Experimental simulation of high temperature sliding contact of hot rolled steel. (January 2016) - Torres, H.; Varga, M.; Widder, F.; Cihak-Bayr, U.; Viskovic, O.; Rodríguez Ripoll, M.
Abstract: Wear plates are used for the alignment of sheet metal during hot rolling of steel. Conditions found during the process, such as the high temperature contact with sheet metal and high sliding speeds are responsible for severe plate wear. Damage characterisation of worn alignment plates showed in particular the onset of microstructure changes beneath the wear grooves and the formation of a mechanically mixed layer in the contact region.The aim of this work is the development of a material selection map for cost-efficient steel grades by means of a new high temperature sliding wear testing. As a result, significant differences in wear behaviour were found between the investigated material classes. Highlights: Microstructural change and MML formation were found at worn guiding plates. Grey cast iron was disadvantageous for the HT sliding contact application. The Fe–Cr–V-based hardfacing showed the highest HT sliding wear resistance. Several tested materials showed almost no wear increase from RT to 700 °C. MML formation provided in-situ wear protection especially at HT.